R for dummies - De Vries, Andrie; Meys, Joris (John Wiley & Sons, Inc., 2015)
This accessible guide is the ideal introduction to R for complete beginners. Learn to master the programming language of choice among statisticians and data analysts worldwide.
Keywords: R (programovací jazyk); matematická statistika; zpracování dat; R (programming language); mathematical statistics; data processing; příručky; handbooks and manuals